The Legal Aspects of Land Auction Process for Former Village Officials Collateral and/or Government-Owned Development Reserve Land - Abdurrahman, Abdurrahman (Jurnal Konstatering, 2022)
This study aims to identify and analyze the legal aspects of the auction process for land that was formerly guaranteed by village officials and/or development reserves belonging to the Bima district government. To find out and analyze the legal consequences for the auctioneers who carry out the auction not based on the laws and regulations regarding auctions. And to find out and analyze the legal consequences of the auction treatise deed from the implementation of an auction that is not based on the laws and regulations regarding auctions. The specification of this research uses descriptive analysis. The type of data used in this study is primary data which includes the 1945 Constitution; Government Regulation Number 28 of 2020; Regulation of the Minister of Finance Number 213/PMK.06/2020; Bima Regent Regulation Number 30 of 2019; Civil Code and Criminal Code, as well as secondary data containing books and other supporting documents. Collection of research data using interview techniques and study of documents or library materials. The data analysis method used in analyzing the data is an interactive model qualitative analysis as proposed by Miles and Huberman. The results of the research show that the process of carrying out the auction as stipulated in the Minister of Finance Regulation Number 213/PMK.06/2020 and the Bima Regent Regulation Number 30 of 2019 there are differences in certain matters. And in practice the implementation of the auction is not in accordance with the provisions of the applicable laws and regulations.Keywords: Auction; Land; Village.Â